Pengaruh Suasana Café dan Variety Product Terhadap Purchase Decision dan Repurchase Intention: Studi pada Konsumen Pesen Kopi Plus Taman Dayu Pandaan - Maula, Inayatul; Wusko, Any Urwatul (Ikatan Da'i Indonesia, 2024)
The purpose of this study was to determine the effect of the Effect of Café Atmosphere and Variety Product on Purchase Decision and Repurchase Intention. This research was conducted at Pesen Kopi Plus Pandaan consumers. This type of research is associative research using a quantitative approach. The number of samples used in the study amounted to 114 respondents. The data collection technique used was a questionnaire. The sample selection for this study used purposive sampling. The data analysis and processing method used is SEM-PLS analysis through Smart PLS 0.4 software. Based on the results of this study, it can be seen that the Café Atmosphere has a positive and significant effect on Purchase Decision, Variety Product has a positive and significant effect on Purchase Decision, Café Atmosphere has a positive and significant effect on Repurchase Intention, Variety Product has a positive and significant effect on Repurchase Intention and Purchase Decision has a positive and significant effect on Repurchase Intention.